Video Steganography Method based on Haar DWT and Spread Spectrum Technique - Elakkiya, D.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
In the development of the network field, the necessity for hiding the information is more important for protecting the information from the third party in an open network. In order to overcome this video stegnography technique is used. It is the profession of hiding the information which helps to conceal the sensitive data than other medium. In stegnography different cover objects are used for video, it can be separate into images and audio and accommodate massive amount of secret information. In this proposed work, introduce the new method for hiding the secret data into a video file using video stegnography technique. In this technique, Haar DWT and spread spectrum to get a stego video. And obtain extraction procedure is similar to embedding procedure vice versa. So that this proposed method is convenient and extracting data easily from stego video.